Breast Cancer-Derived Exosomes Alter Macrophage Polarization via gp130/STAT3 Signaling - Ham, Sunyoung; Lima, Luize G.; Chai, Edna Pei Zhi; Muller, Alexandra; Lobb, Richard J.; Krumeich, Sophie; Wen, Shu Wen; Wiegmans, Adrian P.; Möller, Andreas (Frontiers in Immunology, 2018)
Tumor-derived exosomes are being recognized as essential mediators of intercellular communication between cancer and immune cells. It is well established that bone marrow-derived macrophages (BMDMs) take up tumor-derived exosomes. However, the functional impact of these exosomes on macrophage phenotypes is controversial and not well studied. Here, we show that breast cancer-derived exosomes alter the phenotype of macrophages through the Interleukin 6 (IL-6) receptor beta (glycoprotein 130, gp130)-STAT3 signaling pathway. Addition of breast cancer-derived exosomes to macrophages results in the activation of the IL-6 response pathway, including phosphorylation of the key downstream transcription factor STAT3. Exosomal gp130, which is highly enriched in cancer exosomes, triggers the secretion of IL-6 from BMDMs. Moreover, the exposure of BMDMs to cancer-derived exosomes triggers changes from a conventional towards a polarized phenotype often observed in tumor-associated macrophages. All of these effects can be inhibited through the addition of a gp130 inhibitor to cancer-derived exosomes or by blocking BMDMs exosome uptake. Collectively, this work demonstrates that breast cancer derived-exosomes are capable of inducing IL-6 secretion and a pro-survival phenotype in macrophages, partially via gp130/STAT3 signaling.